The Influence of WFH Policies and It Facilities on Higher Education Performance That Impact on Public Trust in The Bandung Area - Hendar Rubedo; Umi Narimawati; Dewi Indriani; Dadang Munadar; Muhammad Sahlan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to determine the effect of WFH policies and IT facilities on university performance which has an impact on public trust in the Bandung area. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study WFH policy has a significant effect on university performance by 36.2%, hypothesis testing obtained a significance of 0.000 <0.05. IT facilities have a significant effect on university performance by 43.2%, hypothesis testing obtained a significance of 0.000 <0.05. WFH policy and IT facilities simultaneously have a significant effect on university performance by 50.2%, hypothesis testing obtained a significance of 0.000 <0.05. Higher education performance has a significant effect on public trust by 28.2%, hypothesis testing obtained a significance of 0.000 <0 ,05.